Interdental cleaning where we stand today: a questionnaire study - Koregol, Arati C.; Kalburgi, Nagaraj B.; Sulakod, Kavya; singh, Prerna; Puladas, Hannahson (International Journal Of Community Medicine And Public Health, 2022)
Background: Bacterial plaque is etiological factor for initiation of periodontitis. Toothbrushing is necessary for maintaining oral hygiene. However, toothbrushing alone is not enough in interproximal areas. The use of interdental aids was important to clean interdental areas of plaque that forms frequently. Methods: A 35 items questionnaire was structured and distributed among 422 dental under graduate students. The distribution of responses was presented as frequencies and percentage. Results: A total of 422 participants out of whom 5.7% below 20 years 94.3% were 20-25 years. 83 interns and 339 undergraduate students, frequency (%) was more in under graduates compare to interns. The mean knowledge score among undergraduates was 6.80 and in interns was 5.67. Knowledge about interdental cleaning aids was highly significant (p<0.01) among undergraduate students. Conclusions: The overall knowledge and awareness about interdental aids was good. But meticulous planning regarding awareness needs to be followed. The practice regarding interdental aids should be improved, dentist should work closely with the patient to convey message about usage of interdental aids.